User Sentiments And Bankruptcy: The Case Of Cyberpunk 2077 - Adhirajasa, Farrel; Yudha Febrianta , Mochamad; Sudarawerti , Galuh (Action Research Literate, 2024)
This research investigates the correlation between customer sentiments of products and a firm’s probability of bankruptcy. Utilizing the latest version of Altman’s model, user sentiment movements of The Witcher games and Cyberpunk 2077 are compared to CD PROJEKT S.A.s Z’’-score, which includes Working Capital/Total Assets, Retained Earnings/Total Assets, EBIT/Total Assets and Book Value of Equity/Book Value of Total Liabilities for every semester from 2013 to 2023. The results indicate that the relationship between them is weak yet positive, but ultimately insignificant. The literature review investigates the potential cause of this, and concludes that the relationship is not as simple as a bivariate correlation would indicate. Evidence suggests the existence of moderating variables, the possibility that a partial-mediating model is more accurate, and how the industry of the firm could change the nature of customer sentiments.